Wind tunnel demonstration of galloping mitigation with a purely nonlinear energy sink. (January 2021) - Selwanis, Michael M.; Franzini, Guilherme Rosa; Béguin, Cédric; Gosselin, Frédérick P.
Abstract: Galloping is a critical type of flow-induced vibration (FIV) arising on power transmission lines, high rise buildings, pipe and cables bundles in the oil and gas industry. In this paper, we present a purely nonlinear energy sink (NES) that mitigates the galloping of a square prism. The NES is composed of a ball rotating freely in a circular track attached to the prism. The ball's dynamics is coupled to that of the prism in a purely nonlinear way by inertia. We experimentally assess how this simple NES reduces the prism vibration by comparing the prism amplitude responses with and without the NES. A supplementary video presents these experiments, during which the NES ball exhibits different dynamics in three regimes; oscillatory, intermittent, and rotational. We characterize the ball behaviour and its effect on the prism response in each regime. The oscillatory regime appears at low flow speeds at which both the prism and the ball oscillate with small amplitude. The intermittent regime represents a transition mode within a small range of flow speeds and corresponds to a small jump in the vibration amplitude of the prism. The rotational regime appears at higher flow speeds, where the ball oscillates with relatively high angular speeds resulting in a strong modulated response of the prism. The design of the NES allows to easily vary its track dimensions to use a ball of different sizes and masses. Accordingly, we demonstrate the influence of the main NES parameters, which are the ball mass, NES track radius, ball friction, and radial clearance between NES track walls and the rotating ball, on both the prism response and the ball behaviour. The NES we present is directly amenable to mitigate other types of FIV. Graphical abstract: Highlights: A free ball in a circular track acts as a NES and delays the occurrence of galloping. The proposed NES design is robust and works over a large parameter range. The NES experiences three successive response modes with increasing flow speed. The main NES parameters have a significant effect on its behaviour.